2016
DOI: 10.1155/2016/1375606
|View full text |Cite
|
Sign up to set email alerts
|

Exposure top,p′-DDE Induces Morphological Changes and Activation of the PKCα-p38-C/EBPβPathway in Human Promyelocytic HL-60 Cells

Abstract: Dichlorodiphenyldichloroethylene (p,p′-DDE), the most persistent metabolite of dichlorodiphenyltrichloroethane (DDT), is still present in the human population. Both are present in the bone marrow of patients with bone marrow disorders, but thus far there are no studies that assess the capability of p,p′-DDE to affect myeloid cells. The aim of this study was to determine the effect of p,p′-DDE on promyelocytic cell differentiation and intracellular pathways related to this event. p,p′-DDE induced morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…As reported in most populations worldwide [ 24 , 25 , 26 ], our study found that p,p′-DDE was the most abundant compound among the target OCPs. It is the main metabolite of DDT [ 27 ], and the half-life is estimated to be as long as 8.6 years [ 28 ]. Moreover, p,p′-DDE is highly lipophilic, persists for prolonged periods in the environment, and accumulates in the food chain and the tissues of living organisms.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in most populations worldwide [ 24 , 25 , 26 ], our study found that p,p′-DDE was the most abundant compound among the target OCPs. It is the main metabolite of DDT [ 27 ], and the half-life is estimated to be as long as 8.6 years [ 28 ]. Moreover, p,p′-DDE is highly lipophilic, persists for prolonged periods in the environment, and accumulates in the food chain and the tissues of living organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects of DDE, including cellular stress generation [17,72], apoptosis [73], and mitochondrial impairment [74], have been shown in both in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects of DDE, including cellular stress generation [17,72], apoptosis [73], and mitochondrial impairment [74], have been shown in both in vitro and in vivo studies. Present work aimed to further analyze the impact of DDE on cell viability and mitochondrial parameters in an in vitro hepatic cell model (HepG2 cells) in a dose-dependent approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, how LSP1 deficiency is related to CEBP upregulation has not been determined. Previous studies have reported that LSP1 represses the activation of PKCβ in B cells 11 and that PKC activation induces CEBPβ expression in promyelocytic cells 23 , which raises the possibility of a LSP1-PKCβ-CEBPβ axis in LRBs. As expected, the level of phosphorylated PKCβ (pPKCβ) was higher in Lsp1 -/- B cells than in WT B cells ( Fig.…”
Section: Resultsmentioning
confidence: 95%